Knowledge, attitude and practice of healthcare personnel on microorganism transmission via mobile phones - Shaferuddin, Nurul Anis; Alias, Norsyuhada (International Islamic University Malaysia, 2025)
Background: Mobile phones, widely used across all ages and occupations, are high-touch surfaces with the potential to harbour pathogenic microorganisms. Their frequent use in hospital settings enhances medical communication but raises concerns about their role as reservoirs for microbial transmission. This study assessed the knowledge, attitude, and practice (KAP) of healthcare personnel at a hospital in Pahang, Malaysia, regarding microorganism transmission via mobile phones. Methods: A cross-sectional study involving 173 healthcare personnel was conducted using standardized questionnaires. KAP scores were evaluated through true/false questions, Likert scale statements, and practice assessments. Descriptive and inferential analyses were performed to identify factors influencing KAP. Results: Moderate knowledge (59%), good attitude (76.3%), and moderate practices (60.7%) were observed among respondents, with factors such as age and gender influencing scores. Recommendations include implementing UV-C disinfection devices and disinfectant wipes at phone hygiene stations. Conclusion: Enhancing healthcare personnel’s awareness of microorganism transmission via mobile phones is critical to improving hand and mobile hygiene practices, reducing infection risks, and strengthening hospital infection control measures.